1997
DOI: 10.1084/jem.186.9.1597
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of T Cell and Promotion of Natural Killer Cell Development by the Dominant Negative Helix Loop Helix Factor Id3

Abstract: Bipotential T/natural killer (NK) progenitor cells are present in the human thymus. Despite their bipotential capacity, these progenitors develop predominantly to T cells in the thymus. The mechanisms controlling this developmental choice are unknown. Here we present evidence that a member(s) of the family of basic helix loop helix (bHLH) transcription factors determines lineage specification of NK/T cell progenitors. The natural dominant negative HLH factor Id3, which blocks transcriptional activity of a numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
195
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(214 citation statements)
references
References 27 publications
(43 reference statements)
18
195
1
Order By: Relevance
“…Their thymus is characterized by an accumulation of CD4 -CD8 -CD44 + CD25 -thymocytes [44]. Enforced expression of Id3 in human T lineage precursor cells also suppresses thymocyte development [45]. Thus, induction of Id1 expression leading to inhibition of E-protein activity is a likely mechanism for the growth inhibitory effect of BMP-6 on Jurkat Tag cells.…”
Section: Discussionmentioning
confidence: 99%
“…Their thymus is characterized by an accumulation of CD4 -CD8 -CD44 + CD25 -thymocytes [44]. Enforced expression of Id3 in human T lineage precursor cells also suppresses thymocyte development [45]. Thus, induction of Id1 expression leading to inhibition of E-protein activity is a likely mechanism for the growth inhibitory effect of BMP-6 on Jurkat Tag cells.…”
Section: Discussionmentioning
confidence: 99%
“…TCR-transduced CD4 + T-cell clones were detected, which produced both IFNg and IL-4 (Th0), or IFNg (Th1), or IL-4 (Th2). The TCR-transferred CD4 + T cells exerted DBY-specific cytolytic activity upto 26% in a 4-h 51 Cr-release assay, Functional transfer of HLA class II restricted TCR LT van der Veken et al and the specific lysis increased upto 100% after 19 h. Although TCR-transferred CD4 + T-cell clones were obtained that were as cytolytic as the parental JBB4 T cell clone (Figures 2b and 5), variation was observed in the levels of cytolytic activity of the TCR-transferred T-cell clones. We previously demonstrated that TCRtransferred T-cell clones can have different expression levels of the introduced TCR, explaining the observed variation in cytolytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…At the highest CMA concentration (1000 nM) specific target cell lysis was completely blocked (Figure 5b). High amounts of CMA were found not to be toxic to both target cells and T cells, since no increased spontaneous 51 Cr release by the target cells was observed, and no decrease in the number of viable T cells was indicated by eosine staining.…”
Section: Mechanism Of Target Cell Lysis Of the Tcr-transduced T-cell mentioning
confidence: 93%
See 2 more Smart Citations